Analyzing childhood (0–59 months) malnutrition determinants in five West African countries of Gabon, Gambia, Liberia, Mauritania, and Nigeria using a generalized additive mixed model from DHS data - Beni, Reshav; Ramroop, Shaun; Habyarimana, Faustin (Frontiers in Nutrition, 2025)
BackgroundMalnutrition remains a serious public health challenge across West Africa, contributing to high rates of illness and mortality among children. Despite ongoing efforts, its prevalence remains high, underscoring the need to better understand the factors driving poor nutritional outcomes.MethodsThis study analyzed data from Demographic and Health Surveys (DHS) conducted in Gabon, Gambia, Liberia, Mauritania, and Nigeria. Advanced statistical models were used to explore how child, household, and environmental characteristics relate to malnutrition, measured using the Composite Index of Anthropometric Failure (CIAF). Key variables included child age and sex, recent illness, feeding practices, and access to clean water and cooking fuels.ResultsChildren aged 12–60 months had more than twice the odds of being malnourished compared to infants. Male children were more vulnerable than females. Protective factors included access to bottled or sachet water and clean cooking fuels, while recent fever and certain feeding practices—such as formula and fortified food consumption—were associated with increased risk. The analysis also revealed age-related patterns in malnutrition risk, with vulnerability peaking in early toddlerhood.ConclusionThis study highlights the complex interplay of health, environmental, and behavioral factors in child malnutrition across West Africa. The findings can guide evidence-based interventions focused on improving water and energy access, promoting dietary diversity, and integrating nutrition with disease prevention strategies to reduce malnutrition and improve child health outcomes.